Assessment of a simplified insertion technique for intrauterine devices. Issue 1 (31st March 2016) - Christenson, Kamilee; Lerma, Klaira; Shaw, Kate A.; Blumenthal, Paul D.
Abstract: Objective: To explore a simplified technique for intrauterine device (IUD) insertion. Methods: The present prospective longitudinal study enrolled patients aged at least 18 years presenting at the gynecology clinic of Stanford University for IUD insertion between June 1, 2013 and June 30, 2014. No pelvic examination or uterine sounding was performed prior to IUD insertion. Transvaginal ultrasonography was performed immediately after insertion and at 4–6 weeks to confirm device placement. The primary outcome was successful IUD placement. Results: The study enrolled 50 patients. IUD insertion was completed successfully without any cervical manipulation in 40 (80%) participants. Sounding was not needed for any procedures. A cervical dilator was required to locate the internal os for 10 (20%) patients. The mean distance between IUDs and the endometrial verge immediately following insertion was 2.9 mm. IUD insertion was rated "difficult" by the physician performing the procedure in 3 (6%) patients. No perforations were recorded. IUD expulsion occurred in 3 (6%) patients; menorrhagia was the indication for IUD insertion in two of these patients. Conclusion: IUD insertion without prior pelvic examination and sounding was feasible; this technique could reduce the need for instrument use during insertion and, consequently, the pain associated with insertion.